A new atmospheric boundary layer wind tunnel simulation methodology for wind effects on large cooling towers considering wind environment variations. Issue 5 (April 2019) - Cheng, XX; Chen, X; Ge, YJ; Jiang, H; Zhao, L
The traditional atmospheric boundary layer wind tunnel model test practice employs wind fields, the flow characteristics of which are in accordance with the empirical formulae of the atmospheric turbulence presented in Codes of Practice and monographs. However, the empirical formulae presented in Codes of Practice and monographs cannot truthfully reflect the high variations of the realistic atmospheric turbulence which sometimes aggravates wind effects on structures. Based on model tests conducted in a multiple-fan actively controlled wind tunnel, it is found that most wind effects on large cooling towers change monotonically with the increase in free-stream turbulence, and the model test results are more unfavorable for a flow field of low turbulence intensity than for a flow field of high turbulence intensity with respect to the measured coherences. Thus, a new atmospheric boundary layer wind tunnel simulation methodology for wind effects on circular cylindrical structures is proposed to overcome the deficiency of the traditional atmospheric boundary layer wind tunnel model tests. The new simulation methodology includes the simulation of two realistic atmospheric boundary layer flow fields with the highest and the lowest turbulence intensities in the wind tunnel and the envelopment of model test results obtained in the two flow fields (e.g. the mean and fluctuating wind pressure distributions, the power spectral density, the coherence function, and the correlation coefficient). The superiority of the new atmospheric boundary layer wind tunnel simulation methodology over the traditional model test practice is demonstrated by comparing the model test results with the full-scale measurement data.